1974
DOI: 10.2136/sssaj1974.03615995003800040027x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Soybeans to Liming as Related to Soil Acidity, Al and Mn Toxicities, and P in Some Oxisols of Brazil

Abstract: The response of soybeans (Glycine max (L.) Merrill) to the direct and residual effect of liming in relation to soil acidity, Al and Mn toxicities and P availability was studied in five Oxisols of Southern Brazil under successive wheat (Triticum aestivum L.)‐soybean cropping. Yield responses to liming were highly significant due to the high exchangeable Al and extractable Mn, the low pH, exchangeable Ca + Mg, and available P found in these soils. Optimum yields were obtained when liming adjusted Al from 0.1 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…High Al, Fe, and Mn contents in a plant highly affect the biomass and grain yield (Martini et al, 1974;Reich et al, 1981). Similarly, in G. soja in the present study, DW and seed yields in three tolerant accessions were significantly higher than in the intolerant ones, except for seed yield of J-55, probably due to less absorption of toxic minerals from roots under 0.25 LR (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…High Al, Fe, and Mn contents in a plant highly affect the biomass and grain yield (Martini et al, 1974;Reich et al, 1981). Similarly, in G. soja in the present study, DW and seed yields in three tolerant accessions were significantly higher than in the intolerant ones, except for seed yield of J-55, probably due to less absorption of toxic minerals from roots under 0.25 LR (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…Although liming is very effective in reducing Al and Mn toxicity effects in acid soils, liming to bring soil pH to neutrality often requires high rates of application, because of the high buffer capacity provided by the exchangeable Al in these soils (Evans & Kamprath, 1970). Also, massive liming of tropical soils with not only a low fertility, but also a low cation exchange capacity is not only uneconomical and wasteful, but also floods the soil system, bringing serious soil problems in relation to nutrient leaching, fixation and imbalance, rapid organic matter decomposition, destruction of soil aggregates and a high incidence of soil-borne diseases, capable of depressing crop yields even further (Martini et al, 1974).…”
Section: Mineral Toxicity Stressesmentioning
confidence: 99%
“…Bromfield et al (1983) reported that the exchangeable Mn content changed from 4.6 mg kg −1 soil at pH 6.1 to 46.1 mg kg −1 soil at pH 4.8 in trifolium subterraneum dominated pastures. High content of exchangeable Mn (205 mg kg −1 soil) existed in acid Oxisols in Brazil at pH 4.7, plants growing on these soils accumulated large amounts of Mn (1,068 mg kg −1 dry weight) in their tissues, and growth was reduced, liming these soils to pH 5.5 and above decreased the solubility of Mn (59 mg kg −1 soil) and uptake of Mn (193 mg kg −1 dry weight) sufficiently to eliminate the toxicity and increase growth (Martini et al 1974). The solubility and the potential toxicity of Mn to a given crop also depends on other soil properties, including total Mn content, redox potential, microbial activity, organic matter level, aeration, soil drying and heat (Adams 1984;Dolling et al, 2001;Foy 1984).…”
Section: Introductionmentioning
confidence: 99%